2010
DOI: 10.1007/s00467-010-1552-8
|View full text |Cite
|
Sign up to set email alerts
|

Masked hypertension and hidden uncontrolled hypertension after renal transplantation

Abstract: Arterial hypertension is a risk factor affecting graft function in pediatric kidney transplants. Recent pediatric studies reported a high prevalence of hypertension, especially nocturnal hypertension in this population. Data regarding the prevalence of masked hypertension in pediatric patients with kidney transplants are still scarce. The aim of this cross-sectional study was to assess the prevalence of masked and hidden uncontrolled hypertension after renal transplantation. A total of 41 patients (25 males) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 29 publications
9
19
0
Order By: Relevance
“…As in previous studies 19,21,22 , we found no significant association between ABP status and graft function. However, as in the case of LVH, patients with normal BP who did not require antihypertensive medications had less allograft dysfunction than patients taking antihypertensives, even in those whose BP was within normal levels.…”
Section: Discussionsupporting
confidence: 76%
“…As in previous studies 19,21,22 , we found no significant association between ABP status and graft function. However, as in the case of LVH, patients with normal BP who did not require antihypertensive medications had less allograft dysfunction than patients taking antihypertensives, even in those whose BP was within normal levels.…”
Section: Discussionsupporting
confidence: 76%
“…Of the seven subjects with normal BP by office measurements, four had mask hypertension by ABPM. Underestimation of BP control by office measurement was also found in a previous study, which showed 21% were hypertensive by ABPM but normotensive by office BP measurement. Even though our study did not reveal white coat hypertension, the previous studies demonstrated 3%‐10% of RT patients had white coat hypertension .…”
Section: Discussionsupporting
confidence: 78%
“…13.4% (n = 259) respondents who never checked their blood pressure, had been tested to have hypertension. Considering hypertension does not show any eminent symptoms [33] or it could be masked [34], presence of medical check-up is necessary for early detection. This phenomenon was demonstrated in Table 1 where presence of qualified (MBBS) doctors and pharmacies showed significant ( P value < 0.001) association with hypertension.…”
Section: Discussionmentioning
confidence: 99%